Projections from the dorsal and ventral cochlear nuclei to the medial geniculate body - Schofield, Brett R.; Motts, Susan D.; Mellott, Jeffrey G.; Foster, Nichole L. (Frontiers in Neuroanatomy, 2014)
Direct projections from the cochlear nucleus (CN) to the medial geniculate body (MG) mediate a high-speed transfer of acoustic information to the auditory thalamus. Anderson et al., (2006, Eur. J. Neurosci. 24:491) used anterograde tracers to label the projection from the dorsal CN (DCN) to the MG in guinea pigs. We examined this pathway with retrograde tracers. The results confirm a pathway from the DCN, originating primarily from the deep layers. Labeled cells included a few giant cells and a larger number of small cells of unknown type. Many more labeled cells were present in the ventral cochlear nucleus (VCN). These cells, identifiable as multipolar (stellate) or small cells, were found throughout much of the VCN. Most of the labeled cells were located contralateral to the injection site. The CN to MG pathway bypasses the inferior colliculus (IC), where most ascending auditory information is processed. Anderson et al., (2006) hypothesized that CN-MG axons are collaterals of axons that reach the IC. We tested this hypothesis by injecting different fluorescent tracers into the MG and IC and examining the CN for double-labeled cells. After injections on the same side of the brain, double-labeled cells were found in the contralateral VCN and DCN. Most double-labeled cells were in the VCN, where they accounted for up to 37% of the cells labeled by the MG injection. We conclude that projections from the CN to the MG originate from the VCN and, less so, from the DCN. A significant proportion of the cells send a collateral projection to the IC. Presumably, the collateral projections send the same information to both the MG and the IC. The results suggest that T-stellate cells of the VCN are a major source of direct projections to the auditory thalamus.